Effects of shear emulsifying/ball milling/autoclave modification on structure, physicochemical properties, phenolic compounds, and antioxidant capacity of lotus (Nelumbo) leaves dietary fiber - Zheng, Hui; Sun, Yan; Zheng, Tao; Zeng, Yiqiong; Fu, Liping; Zhou, Tingting; Jia, Fan; Xu, Yao; He, Kai; Yang, Yong (Frontiers in Nutrition, 2023)
Lotus (Nelumbo) leaves are rich in polyphenols and dietary fiber, which have the potential as a high-quality fiber material in functional food. However, lotus leaves exhibit dense structure and poor taste, it is vital to develop appropriate modification methods to improve the properties of lotus leaves dietary fiber. In this study, the effects of three modification methods with shear emulsifying (SE), ball milling (BM), and autoclave treatment (AT) on structure, physicochemical properties, phenolic compounds, and antioxidant capacity of lotus leave dietary fiber (LDF) were evaluated. SEM indicated that there were significant differences in the microstructure of modified LDFs. FT-IR spectra and X-ray diffraction pattern of modified LDFs revealed similar shapes, while the peak intensity and crystalline region changed by modification. SE showed the greatest effect on crystallization index. SE-LDF had the highest water holding capacity, water swelling capacity, and bound phenolic content in LDFs, which increased by 15.69, 12.02, and 31.81%, respectively, compared with the unmodified LDF. BM exhibited the most dramatic effect on particle size. BM-LDF had the highest free phenolic and total phenolic contents in LDFs, which increased by 32.20 and 29.05% respectively, compared with the unmodified LDF. Phenolic compounds in LDFs were mainly free phenolic, and modifications altered the concents of flavonoids. The BM-LDF and SE-LDF exhibited higher antioxidant capacity than that of AT-LDF. Overall, SE-LDF showed better physical properties, and BM-LDF showed better bioactive components. SE and BM were considered to be appropriate modification methods to enhance the properties of LDF with their own advantages.